Assessing Public Service Quality in Population Administration at the Bima Population and Civil Registration Office - Hikmatul khairi; Hayat; Langgeng Rachmatullah Putra (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2025)
One of the most important components in the provision of public services is service quality. Reliability, responsiveness, assurance, empathy, and tangibles are the main components of high-quality public services. This study aims to analyze the quality of public service in population administration at the Department of Population and Civil Registration of Bima City, as well as to identify the supporting and inhibiting factors in its implementation. Population administration services represent one of the government’s basic services to the community, such as the issuance of Family Cards (KK), Electronic Identity Cards (E-KTP), and Civil Registration Certificates. The method used in this study was descriptive qualitative, with data collection techniques including observation, interviews, and documentation. Data analysis was carried out using the interactive approach of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the quality of public services in Bima City has not yet been fully optimized. Based on the five dimensions of service quality proposed by Zeithaml, Berry, and Parasuraman namely tangibles.